Child maltreatment, cognitive functions and the mediating role of mental health problems among maltreated children and adolescents in Uganda - Ainamani, Herbert E.; Rukundo, Godfrey Zari; Nduhukire, Timothy; Ndyareba, Eunice; Hecker, Tobias (Child and adolescent psychiatry and mental health, 2021)
Background: Child maltreatment poses high risks to the mental health and cognitive functioning of children not only in childhood but also in later life. However, it remains unclear whether child maltreatment is directly associated with impaired cognitive functioning or whether this link is mediated by mental health problems. Our study aimed at examining this research question among children and adolescents in Uganda. Methods: A sample of 232 school-going children and adolescents with a mean age of 14.03 (SD = 3.25) was assessed on multiple forms of maltreatment using the Maltreatment and Abuse Chronology Exposure—Pediatric Version (pediMACE). Executive functions were assessed by the Tower of London task and working memory by the Corsi Block Tapping task, while mental health problems were assessed using the Child PTSD Symptom Scale for PTSD and the Center for Epidemiological Studies Depression Scale for Children (CES-DC). Results: In total, 232 (100%) of the participant reported to have experienced at least one type of maltreatment in their lifetime including emotional, physical, and sexual violence as well as neglect. We found a negative association between child maltreatment and executive functions (β = − 0.487, p < 0.001) and working memory (β = − 0.242, p = 0.001). Mental health problems did not mediate this relationship. Conclusions: Child maltreatment seems to be related to lower working memory and executive functioning of affected children and adolescents even after controlling for potential cofounders. Our study indicates that child maltreatment the affects children’s cognitive functionality beyond health and well-being
Keywords: Child maltreatment; Cognitive functions; Mental health; East Africa